Condolences strategies by Jordanians to an obituary status update on facebook - Al-Shboul, Yasser; Marlyna Maros (Penerbit UKM, 2013)
Unlike other speech acts such as refusals, apologies, requests and advices, the speech act of giving condolences has not yet been explored adequately. This study intends to investigate the speech act of condolences in Jordanian Arabic that are conveyed via a social network site, i.e. Facebook. The data focused on the condolences made as a response to an obituary status update on a deceased contemporary Jordanian actor in 2011. Based on 678 posted comments, the researchers were able to identify seven major strategies in the commentary; which were: praying for God‟s mercy and forgiveness for the deceased, reciting Quranic verses, enumerating the virtues of the deceased, expressing shock and grief, offering condolences, realizing death is a natural part of life; and using proverbs and sayings. To ensure consistency in the comments, the data was first analysed by the researchers of the present study before three independent raters were invited to analyse the same data sample (condolences). The raters‟ analysis in the commentary reflect the seven major strategies identified by the researchers. The results revealed that the strategies were attributed to the respondents‟ religious orientation (i.e. Islam). Moreover, the findings also indicate that the majority of condolences in Jordanian comments are affiliated to faith and religious beliefs. The results obtained provide useful information to cross-cultural comparison studies and other related studies.